2018
DOI: 10.1055/s-0043-119355
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Multiparametric Ultrasonography Criteria with Digital Subtraction Angiography in Carotid Artery Disease: A Prospective Multicenter Study

Abstract: At laboratories experienced with ultrasound grading of the extracranial ICA, the revised DEGUM multiparametric ultrasonography criteria do not eliminate the need for a confirmatory test for the identification of clinically relevant grades of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
16
1
2
Order By: Relevance
“…Contrary, in a multicentre study, Barlinn and colleagues reported only a moderate agreement and concluded that a confirmatory test is still needed for the grading of ICAS with CDS applying the multiparametric DEGUM ultrasound criteria [29]. In their Bland and Altman diagram, however, their agreement between CDS and DSA seemed to be better when only considering severe (≥ 70% NASCET) ICAS [29] like in our study. Fourthly, we did not assess parameters that are supposed to affect the haemodynamic effect of the ICAS like the blood viscosity (e.g.…”
Section: Discussioncontrasting
confidence: 96%
“…Contrary, in a multicentre study, Barlinn and colleagues reported only a moderate agreement and concluded that a confirmatory test is still needed for the grading of ICAS with CDS applying the multiparametric DEGUM ultrasound criteria [29]. In their Bland and Altman diagram, however, their agreement between CDS and DSA seemed to be better when only considering severe (≥ 70% NASCET) ICAS [29] like in our study. Fourthly, we did not assess parameters that are supposed to affect the haemodynamic effect of the ICAS like the blood viscosity (e.g.…”
Section: Discussioncontrasting
confidence: 96%
“…Indeed, results regarding a subset of 10 carotid occlusions in our study were somewhat less than perfect [1]. Nevertheless, given the fact that the revised DEGUM approach does not provide specific criteria for differentiating between total and near carotid occlusion [2], its low positive predictive value and sensitivity compared to invasive angiography is not surprising, aside from the low number of occlusions.…”
mentioning
confidence: 54%
“…We thank Prof. von Reutern for commenting on our article on the prospective multicenter validation of the revised DEGUM ultrasound criteria for carotid artery stenosis grading [1,2]. We would like to emphasize that our study was not meant to evaluate the ultrasound modality per se, but rather the revised and widely used multiparametric DEGUM approach for ultrasound grading of carotid artery disease as many other approaches have been validated before [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Doppler ultrasonography is a tool combined with B-mode ultrasonography that allows the hemodynamic evaluation of the vessels (Loizou 2014, Barlinn et al 2018, Boyko et al 2018, Mckenna et al 2018, Oglat et al 2018. The common carotid artery originates three important arteries in horses and mules: the internal carotid artery, the external carotid artery and the occipital artery.…”
Section: Introductionmentioning
confidence: 99%